2014
DOI: 10.1155/2014/867075
|View full text |Cite
|
Sign up to set email alerts
|

Free Radicals Scavenging Capacity, Antidiabetic and Antihypertensive Activities of Flavonoid‐Rich Fractions from Leaves of Trichilia emetica and Opilia amentacea in an Animal Model of Type 2 Diabetes Mellitus

Abstract: Trichilia emetica and Opilia amentacea traditional Burkinabe medicinal plants were investigated to determine their therapeutic potential to inhibit key enzymes in carbohydrate metabolism, which has relevance to the management of type 2 diabetes. In vitro and in vivo antioxidant and antihypertensive potential and antilipidemia and antihyperglycemia activities in an animal model of type 2 diabetes mellitus have been studied. The antioxidant activity of the flavonoids from leaves of Trichilia emetica and Opilia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…This study corroborates the results presented by Yarnel and Abascal (2009) who showed that up to 6 g/kg, the T. officinale extract was not toxic in rabbits [29]. Plant extracts and pharmacological substances with LD 50 less than 5 mg/kg bw are classified in the range of highly toxic, those with LD 50 between 5 mg/kg and 5000 mg/kg bw are classified as moderately toxic; while those with LD 50 more than 5000 mg/kg bw are not toxic [30].…”
Section: Discussionmentioning
confidence: 99%
“…This study corroborates the results presented by Yarnel and Abascal (2009) who showed that up to 6 g/kg, the T. officinale extract was not toxic in rabbits [29]. Plant extracts and pharmacological substances with LD 50 less than 5 mg/kg bw are classified in the range of highly toxic, those with LD 50 between 5 mg/kg and 5000 mg/kg bw are classified as moderately toxic; while those with LD 50 more than 5000 mg/kg bw are not toxic [30].…”
Section: Discussionmentioning
confidence: 99%
“…xenobiotics. Pharmacological substances with LD 50 lower than 5 mg/kg body weight are considered highly toxic; those with LD 50 between 5 mg/kg and 5000 mg/kg body weight are classified as moderately toxic; while those with LD 50 greater than 5000 mg/kg body weight are described as being non-toxic [19].…”
Section: Discussionmentioning
confidence: 99%
“…4 At the same time, the research shows that the Trichilia emetica leaf is rich in avonoids, which has the in vivo effect of treating type 2 diabetes by target therapy. 5 It has also been shown that a polyoxyavone from citrus, nobiletin, shows anti-inammatory and anti angiogenic activities in zebrash in vivo. 6 Natural polyphenol avonoid also has anticancer effect, quercetin can inhibit the establishment of tumor in nude mice by subcutaneously inoculating HepG2 cells, and its anticancer effect can be achieved by regulating the expression of cyclin D1 in cancer cells.…”
Section: Introductionmentioning
confidence: 99%